PERCEPTION AND WILLINGNESS TO THE UPTAKE OF COVID-19 VACCINE AMONG HOUSEHOLD-HEADS IN A RURAL COMMUNITY OF SOUTH-WESTERN NIGERIA - ADEWOYE, Kayode Rasaq; OLALUBI, Oluwasogo A; AREMU, Shuaib Kayode; ALAO, Taiye Adeyanju; EKPO, David Sylvanus; IPINNIMO, Tope; ADENIYI, Makinde Adebayo; IBRAHIM, Azeez Oyemomi; SANNI, Taofeek Adedayo; ACHEBE, Chijioke Cosmas; BAKARE, Adewumi; OREWOLE, Tesleem Olayinka; et al. (African Journal of Infectious Diseases (AJID), 2023)
Background: The COVID-19 pandemic and its vaccine have been met with varying perceptions that may have both negative and positive effects on the willingness to uptake the COVID-19 vaccine. The study is set to determine the perception and willingness of the household heads to the uptake of COVID-19 vaccine in a rural community in Southwestern, Nigeria. Materials and Methods: A cross-sectional study was carried out among 409 household heads selected through a multistage sampling technique. The instrument of data collection was a semi-structured interviewer-administered questionnaire using the Health Belief model constructs. Data were analyzed with IBM SPSS version 21.0 and Pearson’s Chi-square test was used to determine the association between perception and willingness to uptake vaccine. P<0.05 was taken as significant at 95% confidence interval. Results: The majority of the unvaccinated respondents in the study were not willing to take the COVID-19 vaccine (60.1%). There was a poor perception of the susceptibility/severity of unvaccinated respondents to COVID-19 infection and a poor perception of the benefit/barrier to the uptake of the COVID-19 vaccine. Perception of susceptibility and severity of COVID-19 infection were statistically related to the willingness to uptake the COVID-19 vaccine. Conclusion: There should be an increase in awareness campaigns to change the perception of people positively to COVID-19 infection and uptake of the COVID-19 vaccine.